2019
DOI: 10.1161/strokeaha.118.023534
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Patients With Peripheral Artery Disease

Abstract: Background and Purpose— Predictors of stroke and transient ischemic attack (TIA) in patients with peripheral artery disease (PAD) are poorly understood. The primary aims of this analysis were to (1) determine the incidence of ischemic/hemorrhagic stroke and TIA in patients with symptomatic PAD, (2) identify predictors of stroke in patients with PAD, and (3) compare the rate of stroke in ticagrelor- and clopidogrel-treated patients. Methods— EUCLID (Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Previous studies have suggested that the risks of stroke and transient ischaemic attack are significantly increased in patients with PAD. 24 However, the association between PAD severity quantified by ABI and CAS is not clear. A prior study involving 5224 Chinese people reported that the proportion of patients with ABI ≤0.9 was higher in the CAS population than in the non-CAS population, suggesting that a low ABI is a significant risk factor for ACAS in male and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the risks of stroke and transient ischaemic attack are significantly increased in patients with PAD. 24 However, the association between PAD severity quantified by ABI and CAS is not clear. A prior study involving 5224 Chinese people reported that the proportion of patients with ABI ≤0.9 was higher in the CAS population than in the non-CAS population, suggesting that a low ABI is a significant risk factor for ACAS in male and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this pilot study, we employed clinical MSOT hybridized with conventional ultrasound as a novel imaging technique for PAD assessment and therapy evaluation. PAD is a serious condition, that carries a substantial morbidity and is additionally considered to be an indicator for coronary artery disease and stroke (24,25). PAD affects more than 200 million people worldwide (26), with significant restraints in life quality and huge healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…As a secondary endpoint, the incidence of stroke differed markedly between the two groups. It has been reported that 2.4% of patients with PAD had ischemic stroke over a period of 30 months ( 15 ). Furthermore, when the baseline ABI value was <0.60, the hazard ratio was 1.309.…”
Section: Discussionmentioning
confidence: 99%